Pengaruh Store Atmosphere, Kualitas Pelayanan, Dan Keberagaman Produk Terhadap Minat Beli Konsumen Pada Minimarket X-Drass - Febtahadul Imam; Muhammad Ridwan Basalamah; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis research was conducted at the Minimarket Klungkung District, Klungkung Regency, Bali. The type of research chosen is explanatory research with quantitative methods. The purpose of this study is to see the impact of store atmosphere, product diversity and service quality on buying interest. The independent variables used are store atmosphere, item diversity, and service quality, while the dependent variable is buying interest. The sample used in this study were 90 participants who were buyers in Klungkung District, Klungkung Regency, Bali. With a questionnaire as data collection. The evaluation method used is the classical assumption test, multiple linear regression analysis, instrument test, determination test, t test and f test using SPSS 16.0 computer software for data processing. The results of this study state that product diversity, service quality and store atmosphere partially affect buying interest and product diversity, store atmosphere and service quality simultaneously affect buying interest. Keywords: Product Diversity, Service Quality, Store Atmosphere and Buying Interest.